Validity and clinical utilization of the Chinese version of the Gotland Male Depression Scale at a men’s health polyclinic - Chu CL (Dove Medical Press, 2014)
Chun-Lin Chu,1–3 Yu Chen,1,3,4 Kun-Hao Jiang,1,3,5 Jiun-Liang Chen,1,3,5 Chin-Pang Lee,1–3 Yeuk-Lun Chau,1,2 Ching-Yen Chen1–3 1Men’s Health Center, 2Department of Psychiatry, Chang Gung Memorial Hospital at Linkou, 3School of Medicine, Chang Gung University, 4Department of Urology, 5Department of Traditional Chinese Medicine, Chang Gung Memorial Hospital at Linkou, Taoyuan, Taiwan Introduction: Symptoms of depression in males, such as aggression and irritability, are different from those in females. However, there are no adequate scales for detecting possible diagnoses in the Chinese population. The aim of this study was to assess whether the Chinese version of the Gotland Male Depression Scale (CV-GMDS) could identify male depression as effectively as the English version. Materials and methods: A total of 231 male outpatients were sampled from a men’s health polyclinic. We used questionnaires to evaluate the characteristics and mood status of participants, including the CV-GMDS, the Chinese version of the Beck Depressive Inventory II (CV-BDI-II), and the Chinese version of the Aging Males’ Symptoms (CV-AMS) scale. Cronbach’s α-coefficient and Levene’s test were used to investigate internal consistency and homogeneity, respectively. External validity was evaluated using Spearman’s correlation coefficient. A factor analysis was conducted to evaluate the conceptual structure of the CV-GMDS, and a regression analysis was used to determine the relationship of the CV-AMS scale with the CV-GMDS and CV-BDI-II. Results: The mean age of the 231 participants was 46.1 years (standard deviation 11.0). Of the participants, 36.8% (n=85) were found to have depression according to the CV-GMDS and 34.6% (n=80) according to the CV-BDI-II. The internal consistency of the CV-GMDS was demonstrated by a Cronbach’s α of 0.933, and the test of homogeneity revealed a P-value of 0.762. The external validity for the CV-GDMS and CV-BDI-II was demonstrated by an intercorrelation of 0.835. The third and fourth items of the GMDS differed from the others, and the CV-GMDS showed a better relationship (R2=0.616) with the CV-AMS scale than the CV-BDI-II did. Conclusion: The CV-GMDS is a satisfactory and suitable psychometric questionnaire for detecting depression among a Chinese-speaking middle-aged or older male population. The results of this study could be used as a basis for investigating specific male depression and aging symptoms. Keywords: male depression, validation, utilization, Gotland Male Depression Scale, Aging Males’ Symptoms scale